Opposing patterns in eating behaviors following bariatric surgery versus lifestyle-induced weight loss - Vuorela, Laura; Berntzen, Bram J.; Muniandy, Maheswary; Saarinen, Tuure; Meriläinen, Sanna; Koivukangas, Vesa; Suojanen, Laura; Groop, Per-Henrik; Rissanen, Aila; Virtanen, Kirsi; Juuti, Anne; Pietiläinen, Kirsi H.; et al. (Public Library of Science (PLoS), 2026)
Objective
This study aimed to investigate 12-month changes in eating behaviors and metabolic outcomes following bariatric surgery or lifestyle-induced weight loss.
Methods
This study is a longitudinal secondary analysis comparing data from two independent prospective cohorts: bariatric surgery (n = 19) and lifestyle-induced weight loss intervention (n = 19). Body weight, body composition (Dual-energy X-ray absorptiometer – DEXA), and metabolic parameters (blood samples, Oral Glucose Tolerance test – OGTT) were measured, and eating behaviors were assessed using validated questionnaires (Three-Factor Eating Questionnaire, Dutch Eating Behavior Questionnaire, Binge-Eating Scale) at baseline, at 5–6 months, and at 12 months after the intervention initiation.
Results
Bariatric surgery produced greater weight loss (surgery −28.1 ± 8.1 kg vs lifestyle −8.9 ± 7.9 kg; p < 0.001) and larger improvements in metabolic markers than lifestyle-induced weight loss. Despite these differences, eating-behavior trajectories diverged. Bariatric surgery was from baseline to 12 months associated with stable or decreased eating restraint, whereas lifestyle-induced weight loss led to an increase in restraint (cognitive restraint: surgery −0.05 ± 0.7 vs lifestyle +6.4 ± 0.9; p < 0.001; restrained eating: surgery −0.7 ± 0.1 vs lifestyle +0.6 ± 0.2; p < 0.001). Both interventions reduced disinhibited eating, binge eating, and external eating. Hunger-related outcomes also improved in both interventions, but with different signatures: surgery was accompanied by reduced hunger perception and cue-reactivity, whereas lifestyle-induced weight loss was characterized by increased reliance on deliberate cognitive/behavioral control strategies. When changes in eating behaviors were analyzed per 1% body weight lost, the opposing pattern in restraint remained significant, and the lifestyle group showed a larger increase in restraint and a greater relative reduction in susceptibility to hunger compared with surgery. Exploratory item-level patterns supported these profiles, suggesting fewer cue-driven triggers to overeat after surgery and greater use of conscious restraint strategies after lifestyle-induced weight loss.
Conclusions
Lifestyle-induced weight loss was associated with increased cognitive restraint, whereas bariatric surgery resulted in stable or decreased restraint. Both interventions decreased hunger sensations, likely through adaptive learning in the lifestyle group and physiological changes after surgery.